UJI EFEKTIVITAS MINYAK CENGKEH TERHADAP TRANSPORTASI KERING DENGAN KEPADATAN TINGGI PADA BENIH IKAN KAKAP PUTIH (Lates calcarifer) - Mbuilima, Megi Rosmiati; Salosso, Yuliana; Lukas, Ade Yulita Hesti (Jurnal Aquatik, 2024)
In an effort to carry out cultivation activities, the obstacle is the availability of seeds is not met, so it is necessary to bring in seeds from other areas. To support cultivation activities, an effective transportation method is needed, one of which is dry system transportation or without water media. By carrying out dry transportation, it can save costs, reduce fish stress, and increase the number of transportation. This study was conducted using a completely randomized design (CRD) with 3 treatments and 3 replications, with the test organism being 5-6 cm white snapper seeds. The treatments tested were different densities, namely treatment A density of 10 fish, treatment B density of 15 fish, and treatment C density of 20 fish. Fish transportation was carried out with previous fish anesthesia, using commercial clove oil anesthetic with a dose of 0.10 ml / liter of seawater. Based on observations of transportation for 1 hour of travel, treatment C was the best treatment, namely with an inductive time of 4 minutes, a duration of unconsciousness of 1 hour, and a sedative time of 18 minutes, resulting in a post-transportation survival rate of 78% and a final maintenance survival rate of 76%. The use of clove oil is effective in maintaining the survival rate after dry transportation and after the end of the research on white snapper (Lates calcarifer) seeds. Keywords: Clove oil, density, life, transportation of dry systems, white snapper